In Vitro Environmental Stresses for Enhancing Withanolides Production in Physalis angulata L. (February 2019) - Mastuti, R; Rosyidah, M
Abstract: Production of secondary metabolites through in vitro culture can be increased by providing environmental stress conditions. Therefore, the objective of this study was to determine the effect of in vitro environment stress by the addition of elicitor on the withanolides production of shoots culture of P. angulata . Two weeks old shoot culture of P. angulata was elicited in either MS medium + biotic elicitor (25, 75, and 125 mg/L chitosan) or abiotic (PEG 2.5, 3, and 5%) for two weeks. The control was MS0 medium without the addition of growth regulators or elicitor. The results of HPLC analysis showed that chitosan elicitor had better effect than PEG. Chitosan was more effective in increasing withanolide content than PEG with a little inhibition of growth. Elicitation with PEG slightly increased withanolide with more inhibiting shoot growth. This result shows that stress manipulation in the in vitro environment through elicitation is potential strategy to improve withanolides production from shoot culture of P. angulata .